INCREASE OF MOTIVATION AND COMPREHENSION OF CHEMISTRY BY STORYTELLING AND PRESENTATION METHODS - Nurul Yuli Fitriyah (Universitas Negeri Surabaya, 2018)
Classroom action research has been carried out in the XII MIA 3 chemistry subjects at SMAN 1 Gurah Kediri Regency with a total of 37 students consist of 11 male students and 26 female students. This research used a storytelling learning method with two cycles. The results showed a significant increase where the average formative value of students in cycle 1 was 53 to 79 in cycle 2. The observation result of the percentage students interest in learning. In the first cycle, reached 35% and increased to 44% in the second cycle. The observation result of the percentage of students attention listening to learning in the first cycle reached 52% and increased to 61%. Similarly, the level of active students participation in the first cycle reached 28% and increased to 45%. These results indicate the learning process using storytelling methods can increase the students interest and think as a whole.